(untitled) (Journal of human and social sciences, 2023)
The study aimed to highlight the topic of administrative development in general, and administrative development models in particular, and to present modern administrative models that enhance the capabilities of researchers and administrators in reorganizing and administrative development. It also aimed to identify the administrative development models applied in the ministry under study, and the extent to which these models are capable of diagnosing and addressing the current administrative reality. The study also sought to identify the advantages and disadvantages of the applied models and to examine the relationship between their effectiveness and the demographic variables of the study sample. To achieve these objectives, the analytical descriptive approach was adopted, and a questionnaire was designed to measure the main dimensions of the research. A stratified random sample of 60 individuals, representing 8% of the research population, was selected from senior, middle, and lower management levels at the ministry’s headquarters in Tripoli and its nearby branches. The study found a positive correlation between the development of administrative performance and the applied administrative development models, indicating that these models significantly influence administrative performance development. However, the study also revealed a low level of work performance system in the ministry due to the inadequacy of the current organizational structure